2020
DOI: 10.32732/jma.2020.9.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Doping Effect on Multifunctionality of SnO2 Nanoparticles

Abstract: In the present study, tin oxide (SnO2) nanoparticles were synthesized by a precursor polymeric method. The obtained nanoparticles were doped with vanadium. The samples were characterized by powder XRD, TEM, optical UV and EPR studies. XRD and TEM showed the rutile crystal structure and its revealed that the lattice cell parameters and particles size were decreased with dopant level. Optical and EPR data confirmed that the doped V enters into SnO2 and distorted the host material symmetry. The films sensing char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…Typically, a larger supercell is connected to larger area for the chemical reactions to take place and can lead to improved photocatalytic activity of SnO 2 . Our approach agrees well with experimental reports 23 , 32 . Specifically, Alvarez-Roca et al 23 investigated at various vanadium doping concentration the X-ray diffraction and transmittance electron microscope for the determination of the structural changes in SnO 2 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Typically, a larger supercell is connected to larger area for the chemical reactions to take place and can lead to improved photocatalytic activity of SnO 2 . Our approach agrees well with experimental reports 23 , 32 . Specifically, Alvarez-Roca et al 23 investigated at various vanadium doping concentration the X-ray diffraction and transmittance electron microscope for the determination of the structural changes in SnO 2 .…”
Section: Resultssupporting
confidence: 93%
“…Our approach agrees well with experimental reports 23 , 32 . Specifically, Alvarez-Roca et al 23 investigated at various vanadium doping concentration the X-ray diffraction and transmittance electron microscope for the determination of the structural changes in SnO 2 . Similar to our study, the found that the V atoms can be incorporated inside the structure of SnO 2 and at low concentrations the cell volume is reduced.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations